Effect of low dissolved oxygen on the viability of juvenile Margaritifera margaritifera: Hypoxia tolerance ex situ. Issue 8 (19th July 2022) - Hyvärinen, Heini S.H.; Sjönberg, Tuomo; Marjomäki, Timo J.; Taskinen, Jouni
Abstract: The decline of endangered freshwater pearl mussel (FPM, Margaritifera margaritifera ) has been attributed to juvenile mortality caused by low concentrations of dissolved oxygen in the stream substrate resulting from fine sediments (siltation) that impede water exchange in the interstitial microhabitat of juveniles. If low oxygen concentration causes recruitment failure of FPMs, knowledge on the oxygen tolerance of juvenile FPMs is essential for the conservation of the species, as it will justify conservation efforts improving water exchange in the bottom gravel. However, the tolerance of low oxygen of FPM juveniles has not been directly studied. Juvenile FPMs (9–11 months old) were exposed in individual chambers equipped with optical oxygen measurement spots to different levels of dissolved oxygen at 19 °C and their viability was monitored for 10 days to assess the acute oxygen tolerance of juvenile FPMs. Oxygen concentration ranged between 8.8 and 6.2 mg L −1 in the high oxygen treatment (control), 5.0–0.4 mg L −1 in the medium treatment, and 1.3–0.04 mg L −1 in the low oxygen treatment (near‐anoxic conditions). Viability of juvenile FPMs depended on the concentration of available dissolved oxygen, such that all juveniles exposed to near‐anoxic conditions were classified as non‐viable, whereas all mussels exposed to high and medium concentrations were viable at the end of the 10 day experiment. Juveniles differed in their ability to tolerate near‐anoxic conditions, so that some individuals survived only 1 day and others survived up to 9 days. This study provides the first direct experimental evidence on the oxygen sensitivity of FPM juveniles and suggests that >10‐day events of very low dissolved oxygen at summer temperatures are fatal to juvenile FPMs, supporting the view that actions preventing low oxygen episodes in the substrate are essential for recruitment, and conservation, of FPMs.